Foliar Nutrient Application: Impact on Kernel Characteristics and Economic Returns in Cashew (Anacardium occidentale L.) CV. Ullal-1" - , Ranjan D N; , Gowtham K M; , Chethankumar C R; , Raviraja Shetty G (Archives of Current Research International, 2025)
A field experiment was carried out during 2023-24 at Krishi Vigyan Kendra, Brahmavara, Udupi. The experiment was laid out in Randomized Complete Block Design comprising of nine treatments, each replicated thrice. Results revealed that trees treated with RDF + Nano urea @ 4ml/L + Borax @ 0.1 % + ZnSO4 @ 0.2 % (T9) recorded maximum Shelling percentage (29.64%), Kernel length (24.83 mm), Kernel width (15.88 mm), Kernel weight (2.62 g), Number of kernels per pound (197.67), Kernel grade (WW-180), yield (0.68 t/ha), Cost of treatment (7105 Rs/ha), Total expenditure (31693 Rs/ha), Gross returns (74800 Rs/ha), Net returns (43107 Rs/ha) and B: C ratio (1.36) .Whereas, minimum was observed in control (T1).Nutrient combination proved highly effective in improving both productivity and returns in cashew cultivation.